Assessment of severe reperfusion injury with T2* cardiac MRI in patients with acute myocardial infarction. Issue 23 (21st October 2010) - O'Regan, Declan P; Ariff, Ben; Neuwirth, Clare; Tan, Yvonne; Durighel, Giuliana; Cook, Stuart A
Abstract : Background: In patients with acute myocardial infarction, restoration of coronary flow by primary coronary intervention (PCI) can lead to profound ischaemia-reperfusion injury with detrimental effects on myocardial salvage. Non-invasive assessment of interstitial myocardial haemorrhage by T2* cardiac MRI (T2*-CMR) provides a novel and specific biomarker of severe reperfusion injury which may be of prognostic value. Objective: To characterise the determinants of acute ischaemia-reperfusion injury following ST elevation myocardial infarction (STEMI) using CMR. Methods and results: Fifty patients with acute STEMI who had been successfully treated by PCI were studied. T2*-CMR was used to identify the presence of reperfusion haemorrhage and contrast enhancement was used to measure microvascular obstruction (MVO) and infarct size. Haemorrhagic ischaemia-reperfusion injury was present in 29 patients (58%) following PCI and occurred despite rapid revascularisation (mean 4.2±3.3 h). Haemorrhage was only present when the infarct involved at least 80% (mean±SD 91±5.3%) of the left ventricular wall thickness. There was a strong association between the extent of MVO and reperfusion haemorrhage (r 2 =0.87, p<0.001). Transmural infarcts (n=43) showed significantly impaired systolic wall thickening at the infarct mid point when reperfusion haemorrhage was present (21.5±16.7% vs 3.7±12.9%), p<0.0001) compared with non-haemorrhagic infarcts. Conclusions: Severe reperfusion injury may occur when there is near-transmural myocardial necrosis despite early and successful revascularisation. Reperfusion haemorrhage is closely associated with the development of MVO. These findings indicate that, once advanced necrosis has developed, the potential for severe myocardial reperfusion injury is significantly enhanced.